Effect of Essential Oil of Tejpat, Black Pepper, and Cardamom as a Natural Food Preservatives for Sweet Orange (Citrus sinensis) Juice - Sagar Mani Paudel; Bishal Thagunna; Deepa Khadka; Rashmi Baral; Deepa Thapa (Biology, Medicine, & Natural Product Chemistry, 2025)
Essential oil of tejpat (Cinnamomum tamala), black pepper (Piper nigrum) and cardamom (Amomum subulatum roxb.) collected by hydro distillation, and were tested as natural food preservative in orange juice (Citrus sinensis). The physiochemical changes such as pH, TSS, acidity, total microbial count, yeast and mold count were evaluated at fix time intervals of 4 hours. for 24 hours. It has been observed that the juice sample infused with black pepper essential oil demonstrated superior preservation of TSS, pH and acidity compared to the other variants. Orange juice supplemented with essential oils maintained the microbial count and yeast and mold count below 100 CFU/ml for up to 24 hours. After 24 hours of storage, all samples surpassed the total microbial count. Among the essential oils, black pepper essential oil demonstrated superior preservation compared to the others.